Beta-blockers to control symptoms in patients with pericarditis. (14th October 2021) - Imazio, M; Andreis, A; Agosti, A; Piroli, F; Casula, M; Paneva, E; Avondo, S; Barberi Squarotti, G; Giustetto, C; De Ferrari, G M
Abstract: Background: Exercise restriction is a non-pharmacological treatment of pericarditis that could reduce symptoms by slowing heart rate (HR). Beta-blockers allow pharmacological control of HR. Aim: To explore the possible efficacy of beta-blockers to improve control of symptoms in patients with pericarditis. Methods: We analysed consecutive cases with pericarditis referred to our centre. Beta-blockers were prescribed on top of standard anti-inflammatory therapy in symptomatic patients (chest pain and palpitations) with rest HR>75 beats/min. The primary end point was the persistence of pericardial pain at 3 weeks. The secondary end point was the occurrence of recurrent pericarditis at 18 months. Propensity score matching was used to generate 2 cohorts of 101 patients with and without beta-blockers with balanced baseline features. A clinical and echocardiographic follow-up was performed at 3 weeks, 1, 3, 6 months and then every 12 months. Results: A total of 347 patients (mean age 53 years, 58% females, 48% with a recurrence, 81% with idiopathic/viral aetiology) were included. Among them, 128 patients (36.9%) were treated with beta-blockers. Peak C-reactive protein values were correlated with heart rate on first observation (r=0.48, p<0.001). Using propensity-score matched cohorts, patients treated with beta-blockers had a lower frequency of symptoms persistence at 3 weeks (respectively 4% vs. 14%; p=0.024) and a trend towards a reduction of recurrences at 18 months (p=0.069). Conclusions: The use of beta-blockers on top of standard anti-inflammatory therapies was associated with improved symptom control. Additional studies are warranted to verify the efficacy of these drugs in this setting. Funding Acknowledgement: Type of funding sources: None.